Pengaruh Kompetensi, Disiplin Kerja dan Motivasi Terhadap Kinerja Pegawai Sekretariat Daerah Pemerintah Kota Palembang - Herfina Saptalia; Muhammad Idris; Diah Isnaini Asiati (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
This study aims to determine the competence, work discipline and motivation for the performance of employees of the Palembang City Government Regional Secretariat. The object of this study is the Employee of the Regional Secretariat of the Palembang City Government. The research method used is associative research using primary and secondary data. The population in this study was 202 employees at the Palembang City Government Regional Secretariat; the sample was taken using the Slovin formula, so the number of samples used was 135 employees. Sampling technique with probability sampling with the cluster sampling method. The analysis technique used is multiple linear regression. The results of this study show that:1)simultaneously, competence, work discipline and motivation have a significant effect on the performance of employees of the Palembang City Government (Regional Secretariat.2) competence has a significant effect on the performance of employees of the Palembang City Government Regional Secretariat. 3) Work discipline significantly affects the performance of employees of the Palembang City Government Regional Secretariat. 4) motivation has a significant effect on the performance of employees of the Palembang City Government Regional Secretariat